Continuous Analoque of Dynamic Programming Allocation Process - Rutkauskas, P.; Bistrickas, V. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Руткаускас, В. Бистрицкас. Непрерывный аналог процесса распределения динамического программирования P. Rutkauskas, V. Bistrickas. Dinaminio programavimo pasiskirstymo proceso tolydinis analogas